Mangrove vegetation enhances soil carbon storage primarily through in situ inputs rather than increasing allochthonous sediments. (June 2018) - Xiong, Yanmei; Liao, Baowen; Wang, Faming
Abstract: The role of soil carbon (C) in coastal wetlands as a net sink is related to the relative abundance of autochthonous versus allochthonous C. We aimed to investigate soil C sources and the pathways by which mangrove vegetation enhances soil C accumulation. We sampled soil to 1 m depth in seven oceanic mangrove forests and an adjacent un-vegetated mudflat at Dongzhai Bay, China. Stable C isotope technique was used to separate autochthonous and allochthonous C sources. Autochthonous C accounted for 27–97% of soil C stock in the top meter. Soil C density was 1.1–3.6 times higher in mangroves than in the mudflat. Among the increased soil C in mangroves relative to mudflat, autochthonous C accounted for 65–100% of the increments. The results suggest that mangrove vegetation enhances soil C storage primarily through in situ inputs, therefore the substantial soil C stocks commonly found in mangroves play an important role in sequestering atmospheric CO2 . Graphical abstract: Highlights: Mangrove derived C accounted for 27–97% of top meter soil C stock in mangroves Soil C stock was 1.1–3.6 times higher in mangroves than in adjacent mudflat. Mangrove C explained 65–100% of soil C increments in mangroves relative to mudflat Allochthonous soil C stock in mangroves was similar or lower than that in mudflat. Adjacent mudflat soil C was a good proxy of allochthonous soil C in mangroves.